IDENTIFICATION OF PATHOGENIC BACTERIA OF TILAPIA (Oreochromis niloticus) IN SUBDISTRICT MARPOYAN DAMAI PEKANBARU - Dicky Azwar Lubis; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was done in April - Juni 2014 in Fish Disease Parasite and Laboratories and an Experiment of the Faculty of Fisheries and Marine Science University of Riau. This study aims to determine the types of pathogens that attack tilapia in District Marpoyan Damai Pekanbaru. The benefits of this research is to provide information to farmers about the types of pathogens in tilapia, so it can be the prevention of disease. The method used in this study is a survey method by taking samples in the field and analyzed in the laboratory. The amount of bacteria found from both the ponds was six species. Bacteria found in a pond one these were Aeromonas hydrophila, Basillus sp, Pseudomonas sp and Streptococcus sp. Meanwhile bacteria found in a pond two these were Basillus sp, Stapyhilococcus sp, and Edwardsiella tarda.Keywords: Pathogenic Bacteria, Tilapia,